Overview of Jute Fibre as Thermoplastic Matrix Polymer Reinforcement - Tezara Cionita, Tezara Cionita; Mohamad Hamdan, Mohammad Hazim; Januar Parlaungan Siregar, Januar Parlaungan Siregar; Deni Fajar Fitriyana, Deni Fajar Fitriyana; Junid, Ramli; Wong Ling Shing, Wong Ling Shing; Jaafar, Jamiluddin; Agustinus Purna Irawan, Agustinus Purna Irawan; Teuku Rihayat, Teuku Rihayat; Rifky Ismail, Rifky Ismail; Athanasius Priharyoto Bayuseno, Athanasius Priharyoto Bayuseno; Emilianus Jehadus, Emilianus Jehadus (Tech Science Press, 2024)
Recent decades have seen a substantial increase in interest in research on natural fibres that is aligned with sustainable development goals (SDGs). Due to their renewable resources and biodegradability, natural fiberreinforced composites have been investigated as a sustainable alternative to synthetic materials to reduce the usage of hazardous waste and environmental pollution. Among the natural fibre, jute fibre obtained from a bast plant has an increasing trend in the application, especially as a reinforcement material. Numerous research works have been performed on jute fibre with regard to reinforced thermoset and thermoplastic composites. Nevertheless, current demands on sustainable materials have required new developments in thermoplastic composites. In this paper, the author reviews jute plants as reinforcement materials for thermoplastic matrix polymers. This review provides an overview of the sustainability of jute plants as reinforcement material for thermoplastic matrix polymers. The overview on jute based thermoplastic composites focused on the thermal behavior and mechanical properties. Apart from physical, chemical, and mechanical properties, the study also covers the current and perspectives for future research challenges faced by the researchers on jute fibre reinforced thermoplastic composites.